2006
DOI: 10.1366/000370206778664581
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Multivariate Classification Models between Laboratory and Process Near-Infrared Spectrometers for the Discrimination of Green Arabica and Robusta Coffee Beans

Abstract: Analogous to the situation found in calibration, a classification model constructed from spectra measured on one instrument may not be valid for prediction of class from spectra measured on a second instrument. In this paper, the transfer of multivariate classification models between laboratory and process near-infrared spectrometers is investigated for the discrimination of whole, green Coffea arabica (Arabica) and Coffea canefora (Robusta) coffee beans. A modified version of slope/bias correction, orthogonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 25 publications
0
26
0
1
Order By: Relevance
“…Alternatives to local models may be the use of flexible multivariate regression models such as partial least squared regression (PLSR) [32], direct and piecewise direct standardization [28,35,36], neural networks [30], orthogonal least squares [27] and slope/bias corrections [26,27]. Multivariate calibration strategies offer more flexibility than the use of a single vector, because individual calibration ratios are calculated for each spectrum.…”
Section: Alternative Methodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatives to local models may be the use of flexible multivariate regression models such as partial least squared regression (PLSR) [32], direct and piecewise direct standardization [28,35,36], neural networks [30], orthogonal least squares [27] and slope/bias corrections [26,27]. Multivariate calibration strategies offer more flexibility than the use of a single vector, because individual calibration ratios are calculated for each spectrum.…”
Section: Alternative Methodologymentioning
confidence: 99%
“…In the field of calibration this is commonly referred to as standardization of instruments [25]. Standardization and calibration transfers have been applied to correct for instrument differences in near infrared spectroscopy [25][26][27], nuclear magnetic resonance spectroscopy [28,29] pyrolysis mass spectra [30,31] and gas sensor arrays [32]. Because of different noise patterns, standardization and calibration methods are transferable only to a limited degree between these techniques.…”
Section: Introductionmentioning
confidence: 99%
“…84 Both modified SBC and orthogonal signal correction (OSC) methods can be used to correct NIR spectra used in a classification model to allow transfer of the classification between a laboratory and a process instrument. Given the close similarity of regression and some classification models, it is not too surprising that some of the same considerations discussed above in the context of calibration models also apply to a classification model.…”
Section: Standardization For Transfer Of Classification Modelsmentioning
confidence: 99%
“…Classical point-wise NIR spectroscopy has been widely used to discriminate Arabica and Robusta species, both on green coffee [35,36] and roasted coffee [37,38]. Moreover some research works have been also reported where hyperspectral imaging is used to characterize these coffee species [39,40].…”
Section: Introductionmentioning
confidence: 99%